Sodium coupled glucose co-transporters contribute to hypothalamic glucose-sensing - O'Malley, Dervla (2006)
Specialised neurons within the hypothalamus have the ability to sense and respond to changes in ambient glucose concentrations. We investigated the mechanisms underlying glucose-triggered activity in glucose-excited (GE) neurons, using primary cultures of rat hypothalamic neurons monitored by fluorescence calcium imaging. 35% (738/2139) of neurons were excited by increasing glucose from 3 to 15mM, but only 9% (6/64) of these GE neurons were activated by tolbutamide, suggesting the involvement of a K(ATP) channel-independent mechanism. α-Methylglucopyranoside (αMDG, 12mM), a non-metabolisable substrate of sodium glucose co-transporters (SGLTs), mimicked the effect of high glucose in 67% of GE neurons, and both glucose and αMDG-triggered excitation were blocked by Na(+) removal or by the SGLT inhibitor, phloridzin (100nM). In the presence of 0.5mM glucose and tolbutamide, responses could also be triggered by 3.5mM αMDG, supporting a role for an SGLT-associated mechanism at low as well as high substrate concentrations. By RT-PCR, we detected SGLT1, SGLT3a, SGLT3b in both cultured neurons and adult rat hypothalamus. Our findings suggest a novel role for SGLTs in glucose-sensing by hypothalamic GE neurons.